Longitudinal growth on an everolimus- versus an MMF-based steroid-free immunosuppressive regimen in paediatric renal transplant recipients - Billing, Heiko; Burmeister, Greta; Plotnicki, Lukasz; Ahlenstiel, Thurid; Fichtner, Alexander; Sander, Anja; Höcker, Britta; Tönshoff, Burkhard; Pape, Lars (Transplant international, 2013)
Concerns have been raised that mammalian target of rapamycin inhibitors in pediatric transplant recipients might interfere with longitudinal bone growth by inhibition of growth factor signaling and growth plate chondrocyte proliferation. We therefore undertook a prospective nested, case-control study on longitudinal growth over 2 years in steroid-free pediatric renal transplant recipients. Fourteen patients on a steroid-free maintenance immunosuppressive regimen consisting of low-dose everolimus (EVR) in conjunction with low-dose cyclosporine (CsA) were compared to a matched cohort of 14 steroid-free patients on a standard dose mycophenolate mofetil (MMF) regimen in conjunction with a standard dose calcineurin inhibitor (CNI). The mean change in height standard deviation (SD) score in the first study year was 0.31 ± 0.71 SD score in the EVR group compared to 0.31 ± 0.64 SD score in the MMF group (P = 0.20). For the entire study period of 2 years, the change in height SD score in the EVR group was 0.43 ± 0.81 SDS compared to 0.75 ± 0.85 SDS in the MMF group (P = 0.32). The percentage of prepubertal patients experiencing catch-up growth, defined as an increase in height SD score ≥0.5 in 2 years, was similar in the EVR group (5/8, 65%) and the MMF group (6/8, 75%; P = 1.00). Longitudinal growth over 2 years in steroid-free pediatric patients on low-dose EVR and CsA is not different to that of a matched steroid-free control group on an immunosuppressive regimen with standard-dose CNI and MMF. Hence, low-dose EVR does not appear to negatively impact short-term growth in pediatric renal transplant recipients.
Gesehen am 25.11.2020